Counseling in Treating Fever in Toddler-aged Child - Perbawati, Dinar; Hidayah, Silvirian Nur (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
Abstract: Background: toddler-aged 1-3 are often accompanied by several diseases in its growth and development. Almost all infectious diseases have a fever in their reaction. Fever has been defined as an above-normal increase in body temperature above the norm, the 37.5 degrec. Parents with fever children typically behave and attempts to lower their body temperature so that a parent will respond, which includes seeking medical attention, taking personal precautions, sometimes do nothing or do nothing about it (no action). The mother's response and behavior are affected by several factors including her knowledge level, education level, work status, age, attitude and social status. Method: Implementation can be made by counseling the mother on how appropriate ways to administer treatment during a fever. Perform a correct warm compress demonstration when a child's temperature rises and suggests the mother to apply them when the child has a fever. Results: Followed initial to final counseling activities carefully, noticed, and demonstrated appropriate areas for a warm compress. Conclusion: The treatment of fever in children of occupational age is affected by several factors: predisposition, contributing factors, contributing factors. The mother can do good with fever if the information is obtained.. Keywords: Treating Fever; Fever; Toddler-aged Child Abstrak: Latar belakang: Anak usia toddler yaitu usia 1-3 tahun sering disertai beberapa penyakit dalam pertumbuhan dan perkembangannya. Hampir dari semua penyakit infeksi memiliki demam sebagai reaksinya. Orang tua yang memiliki anak demam biasanya akan timbul perilaku dan usaha untuk menurunkan suhu tubuh anak sehingga muncul respon orang tua, yang diantaranya mencari pengobatan ke pelayanan kesehatan, melakukan tindakan pengobatan sendiri, kadang tidak bertindak atau tidak melakukan apa-apa (no action). Respon dan perilaku ibu tersebut dipengaruhi oleh beberapa faktor yang mencakup diantaranya, tingkat pengetahuan, tingkat pendidikan, status pekerjaan, umur, sikap dan tingkat ekonomi ibu. Metode : Implementasi dilakukan dengan memberikan konseling kepada ibu tentang bagaimana cara yang tepat untuk memberikan penanganan pada saat anak mengalami demam. Melakukan demonstrasi kompres hangat yang benar saat suhu tubuh anak naik dan menyarankan ibu untuk mengingat hal-hal yang telah disampaikan dan menerapkannya saat anak mengalami demam. Hasil : Mengikuti kegiatan konseling dari awal hingga akhir dengan seksama, memperhatikan, dan memperagakan tempat-tempat yang tepat untuk kompres hangat Kesimpulan: penanganan demam pada anak usia toddler terpengaruhi oleh beberapa faktor yaitu faktor predisposisi, faktor pendukung, faktor pendukung. ibu dapat melakukan penanganan demam secara baik jika informasi yang didapatkan juga baik. Kata kunci: Penanganan Demam, Demam, Anak Usia Toddler